The Effect of Buy 1 Get 1 Promotion and Interpersonal Communication Skill Towards Impulse Buying Behavior - Elviara Dwi Raissa; Fahira Dwinda Rachmadiani; Sherena Jessica Wijaya; Muhammad Aras (Syntax Corporation, 2022)
Modern fashion trends that are developing in Indonesia today are inseparable from the emergence of local brands. In fact, some local Indonesian fashion brands can compete in the international market. One of the original Indonesian fashion brands that appeared in the world fashion market is Erigo. Erigo through the Instagram account @erigostore covered its content in such a way as to inform various offers to market its products. Some of the marketing techniques carried out by Erigo through the @erigostore Instagram account are sales promotion and personal selling. This study aims to determine how much sales promotion and personal selling affect the impulsive buying behavior of followers of the @erigostore Instagram account. This research uses quantitative research methods, where data are analyzed using multiple regression analysis. The results of this study found that sales promotion and personal selling simultaneously influenced the impulsive buying of Instagram account followers @erigostore positively and significantly. In other words, an increase in sales promotion and personal selling will be followed by an increase in the impulsive buying of followers of the Instagram account @erigostore. These two variables influence impulsive buying by 83%.